Efficacy and Safety of E6011, an Anti‐Fractalkine Monoclonal Antibody, in Patients With Active Rheumatoid Arthritis With Inadequate Response to Methotrexate: Results of a Randomized, Double‐Blind, Placebo‐Controlled Phase II Study. Issue 4 (18th February 2021) - Tanaka, Yoshiya; Takeuchi, Tsutomu; Yamanaka, Hisashi; Nanki, Toshihiro; Umehara, Hisanori; Yasuda, Nobuyuki; Tago, Fumitoshi; Kitahara, Yasumi; Kawakubo, Makoto; Torii, Kentaro; Hojo, Seiichiro; Kawano, Tetsu; et al.
Abstract : Objective: To evaluate the efficacy and safety of E6011, a humanized IgG2 monoclonal antibody against human fractalkine (FKN), in a phase II, double‐blind, placebo‐controlled study in rheumatoid arthritis (RA) patients. Methods: Patients with moderate‐to‐severe RA who had an inadequate response to methotrexate were randomly assigned to a placebo group or to E6011 100‐mg, 200‐mg, or 400/200‐mg groups at a 2:1:2:2 ratio. During the 24‐week period, patients received the study drug subcutaneously at weeks 0, 1, and 2 and then once every 2 weeks. The primary end point was the American College of Rheumatology 20% improvement criteria (ACR20) response rate at week 12. Results: Study drugs were administered to 190 patients (placebo, n = 54; E6011 100 mg, n = 28; E6011 200 mg, n = 54; E6011 400/200 mg, n = 54), and 169 patients completed treatment. A significant difference from placebo was not found in ACR20 response rates at week 12 (37.0% [placebo], 39.3% [100 mg], 48.1% [200 mg], and 46.3% [400/200 mg], using nonresponder imputation). As a secondary end point, ACR20 response rate in the 200‐mg and 400/200‐mg groups attained statistical significance at week 24 (35.2% [placebo], 39.3% [100 mg], 53.7% [200 mg], and 57.4% [400/200 mg]). Subsequent exploratory subgroup analysis revealed greater efficacy of E6011, particularly in patients with a higher baseline proportion of CD16+ monocytes; ACR20 response rates in this patient subgroup at week 24 were 30.0% (placebo), 46.7% (100 mg), 57.7% (200 mg), and 69.6% (400/200 mg). E6011 administered for 24 weeks was well tolerated. Conclusion: This is the first evidence that E6011, a novel cell trafficking inhibitor targeting the FKN–CX3 CR1 interaction, is modestly effective with 24 weeks of treatment in RA patients, although the primary end point was not met.